Effects of water-cooled cover on physiological and production parameters of farrowing sows under hot and humid climates - Zhenzhen, Pang; Baoming, Li; Weichao, Zheng; Baozhong, Lin; Zuohua, Liu (International Journal of Agricultural and Biological Engineering, 2016)
The hot and humid climates, as encountered in the southern region of China with the open housing, can adversely impact the sows undergoing heat stress during the most vulnerable period at lactation. Hence, a water-cooled cover system (WCCs) for local cooling has essential practical value to improve productivity. The WCCs was developed for the sow crate of lactating sows separately, which performance was validated with the cooling efficiency in the sow occupied zone (SOZ) and physiological parameters. The results showed that the WCCs for the farrowing sows using aluminium plastic tubes connected in series could reach an appropriate cooling performance in adjacent units. The WCCs could decrease the SOZ air temperature by 3.0°C-4.5°C under the extremely hot climate when the indoor air temperature was 37°C, and maintain a suitable range (25°C-30°C) under the typical hot climate (<35°C). The respiration rate and skin temperature of farrowing sows had no significant difference between treatment group (WCC) and control group (sprinkle cooling) when the air temperature was below 30°C, but had a significant difference (p<0.05) when air temperature rose above 30°C. The control sows drank more during hot weather, and the feed intake was significantly lower than the sows with the WCCs (p<0.01). It was concluded that the WCCs could alleviate the heat stress of farrowing sows during typical hot climate.Keywords: localized cooling, heat stress, farrowing sow, water-cooled cover, hot and humid climateDOI: 10.3965/j.ijabe.20160904.1858Citation: Pang Z Z, Li B M , Zheng W C, Lin B Z, Liu Z H. Effects of water-cooled cover on physiological and production parameters of farrowing sows under hot and humid climates. Int J Agric & Biol Eng, 2016; 9(4): 178－184.